Новата етичка аксиологија во политиката - Донев, Дејан (Правен факултет „Јустинијан I“, Скопје, 2013)
If we want to make a right choise about the dillema - does political ethics is reality or it is just an oximoron, we must make a summary on the new moral values in politics, must make an observation of the new ethical axiology in politics. First of all, we have to start from the analysis on the connection between ethics and politics today, because they, after a long period of separation, are observing again in common relation cause their essence is historically and substantially connected. The basic form of connection between politics and ethics we find since Antique in Plato and Aristotle’s work, in their practical philosophy, where beside ethics, there are politics and economy. There we find the grounding on the ideal of “oikos” as an ideal of good common living. The breakdown of the faith, which overtook the connection between ethics and politics, generally the practical philosophy, is breakdown that overtook the whole society and history. This especially is applying on new era and the beginning of the contemporary world in which, from Hobbs till today, the connection between ethics and politics is questioned. The rehabilitation of the practical philosophy from 1930 wanted to show how can we return toward successful politics and common life. From here, if we want to outrival the situations in life and politics, we have to set up again the philosophical-political-ethical question for the new ethical values in politics. Besides basic values of today’s social-political system, like Democracy, Progress, Understanding between people, Ethics and Truth, a big number of ethical values became basic political values and norms cause of the reviving on specific morality in politics which means care for the people, unviolation of ethical standards, making efforts for progress, as well as managing the future develop. Between them, the most important are: Peace, Corporation, Understanding between the people and nations, Tolerance, Human rights, as well as the concept of Freedom. Can this new ethical axiology confirms the fact about political ethics as a reality or as an oximoron!?
New ethical axiology in politics
Годишник на Правниот факултет „Јустинијан Први“, Том 47-48, во чест на 18 години од основањето на политички студии
Keywords: axiology, ethics, politics, values